Bimbingan Kelompok untuk Membangun Pikiran Positif dalam Upaya Meningkatkan Kepercayaan Diri Remaja - Zhenata Andiny; Mumtaz Afridah; Daffa Azzahra; Makhmudah Amalia Syafitri (STKIP PGRI SUMENEP, 2025)
Positive thinking is a major asset in instilling self-confidence. Positive thinking is the ability to assess everything from a positive side. This study aims to determine the problem of lack of self-confidence influenced by negative thoughts towards 6 students of GRAHA Yatim & Dhu’afa Yayasan Harapan Rabbani Cirebon before and after group guidance. Group guidance is a counseling guidance service that utilizes group dynamics to discuss actual topics. This research uses a qualitative approach. A qualitative approach is research on research that is descriptive and has a tendency to use analysis. Based on the research conducted, that initially the client had problems with self-confidence caused by negative thoughts. After group guidance, it can be seen that clients who tend to have the lowest self-confidence have begun to dare to speak in public. Further treatment is needed to achieve maximum results. Keyword: Group Guidance, Positive Thinking, Self-confidence